Vitamin C content in essential oils and nutrient content in fruits of physalis minima (Letup-Letup) - Amy Shakila Hamidi (Bintulu, Sarawak : Universiti Putra Malaysia, 2015)
Physalis minima (letup-letup) is a native gooseberry which belongs to the family of Solanaceae and is an annual weed, herbaceous plant, shrubs and usually found in the tropics. In Malaysia, Physalis minima was treated as a weed that is commonly found in Peninsular Malaysia which grow wild and requires full sun. Physalis minima are also known as “letup-letup” in Malaysia. The essential oil was obtained from fruits of P. minima. The methods are used for the extraction to get essential oil from fruits is alcohol distillation and water distillation. The objective of this study were vitamin C content and nutrient content in P. minima fruits produced under cultivation and it also to identify the best extraction method to extract essential oil of P. minima fruits. The treatment was divided to two method of extraction. Each the treatment has 3 replications to get more accurate data. The data (essential oil, vitamin C, nitrogen (N), phosphorus (P) and potassium (K)) be obtained after the fruits are harvested. The results showed that the extraction was done using alcohol were better in maintaining vitamin C content in the essential oil derived from the fruit P. minima. As a conclusion, the essential oil can be obtained using thimble extraction method using different solvents. However, best solvent for extraction was methanol because it could retain more vitamin c content.
Project Paper
Keywords: Vitamin C; Wild flowers